2021
DOI: 10.3389/fnhum.2021.762343
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of Whole Brain ALFF/fALFF and Degree Centrality in Adolescents With Depression and Suicidal Ideation After Electroconvulsive Therapy: A Resting-State fMRI Study

Abstract: Major depressive disorder (MDD) is one of the most widespread mental disorders and can result in suicide. Suicidal ideation (SI) is strongly predictive of death by suicide, and electroconvulsive therapy (ECT) is effective for MDD, especially in patients with SI. In the present study, we aimed to determine differences in resting-state functional magnetic resonance imaging (rs-fMRI) in 14 adolescents aged 12–17 with MDD and SI at baseline and after ECT. All participants were administered the Hamilton Depression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 61 publications
1
18
1
Order By: Relevance
“…Mao et al reported an elevated ReHo value in the right precentral gyrus in adolescent MDD relative to HCs (14), which is in line with our results. Further, fALFF in the right precentral gyrus in depressed adolescents with suicidal ideation was found to be significantly decreased after electroconvulsive therapy (17), and higher FC between the right precentral gyrus and left habenula was also noted in individuals with MDD or bipolar disorder and a history of SA relative to patients without SA (45). Taken together with the above studies, our findings suggest that the right precentral gyrus may be involved in the neural circuitry of suicide in MDD.…”
Section: Discussionmentioning
confidence: 99%
“…Mao et al reported an elevated ReHo value in the right precentral gyrus in adolescent MDD relative to HCs (14), which is in line with our results. Further, fALFF in the right precentral gyrus in depressed adolescents with suicidal ideation was found to be significantly decreased after electroconvulsive therapy (17), and higher FC between the right precentral gyrus and left habenula was also noted in individuals with MDD or bipolar disorder and a history of SA relative to patients without SA (45). Taken together with the above studies, our findings suggest that the right precentral gyrus may be involved in the neural circuitry of suicide in MDD.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that long-distance connections and local brain neural activities often occur simultaneously and interact (47,48). In addition, previous studies have documented that depression symptoms are negatively correlated with local neural activity in the brain (49,50). Therefore, the inter-modular connections between the FPN and CON that decrease with the increase in depressive symptoms may reflect the decrease in local neural activity in the brain, rather than long-distance abnormal changes.…”
Section: Discussionmentioning
confidence: 94%
“…The latest findings of structural MRI can use the volume and thickness of cortical gray matter, subcortical volume, and the integrity of white matter bundle to examine the brain structure (or anatomical) changes in neural circuits (10). In the related study of major depressive disorder, it is found that ECT has a certain effect (1). After ECT, amplitude of low frequency fluctuation (ALFF) and fractional ALFF (fALFF) of the right precentral gyrus decreased significantly, and there was a significant correlation between the changes of depressive symptom and ALFF, and between suicidal ideation and fALFF.…”
Section: Major Depressive Disordermentioning
confidence: 99%